Pim1 Kinase Inhibitors Exert Anti-Cancer Activity Against HER2-Positive Breast Cancer Cells Through Downregulation of HER2 - Wang, Bo-Wei; Huang, Chih-Hao; Liu, Liang-Chih; Cheng, Fang-Ju; Wei, Ya-Ling; Lin, Yueh-Ming; Wang, Yu-Fei; Wei, Ching-Ting; Chen, Yeh; Chen, Yun-Ju; Huang, Wei-Chien (Frontiers in Pharmacology, 2021)
The proviral integration site for moloney murine leukemia virus 1 (Pim1) is a serine/threonine kinase and able to promote cell proliferation, survival and drug resistance. Overexpression of Pim1 has been observed in many cancer types and is associated with the poor prognosis of breast cancer. However, it remains unclear whether Pim1 kinase is a potential therapeutic target for breast cancer patients. In this study, we found that Pim1 expression was strongly associated with HER2 expression and that HER2-overexpressing breast cancer cells were more sensitive to Pim1 inhibitor-induced inhibitions of cell viability and metastatic ability. Mechanistically, Pim1 inhibitor suppressed the expression of HER2 at least in part through transcriptional level. More importantly, Pim1 inhibitor overcame the resistance of breast cancer cells to HER2 tyrosine kinase inhibitor lapatinib. In summary, downregulation of HER2 by targeting Pim1 may be a promising and effective therapeutic approach not only for anti-cancer growth but also for circumventing lapatinib resistance in HER2-positive breast cancer patients.